Effects of mixed cropping and inoculants on yield and quality of forage under different inter cropping ratios of oat and field pea (Bangladesh Journal of Botany, 2024)
Using forage oat and field pea, this study was conducted  to explore the effects of sole and mixed cropping patterns at varying ratios, and microbial inoculant application. The aim was to reveal the comprehensive effects of mixed cropping patterns and microbial inoculation on the above-ground biomass, forage yield, and nutritional quality. The results indicated that mixed cropping significantly increased the above-ground biomass of both oats and field peas. With microbial inoculation, mixed cropping increased dry hay yield by 21.81%, 18.31%, 13.33%, and 10.05%;  crude protein by 9.4%, 16.44%, 14.98%, and 4.18%, and crude fat by 8.22%, 2.9%, 14.81%, and 5.59% respectively, compared to sole cropping. Additionally, neutral and acid detergent fiber contents decreased by 2.94% and 1.89% on average in mixed crops. These findings suggest that mixed cropping with microbial inoculants can significantly increase forage nutritional quality and yield, offering a scientific basis for efficient forage crop utilization.Bangladesh J. Bot. 53(4): 903-911, 2024 (December)